Low temperature decreases bone mass in mice: Implications for humans. Issue 3 (6th September 2018) - Robbins, Amy; Tom, Christina A. T. M. B.; Cosman, Miranda N.; Moursi, Cleo; Shipp, Lillian; Spencer, Taylor M.; Brash, Timothy; Devlin, Maureen J.
Abstract: Objectives: Humans exhibit significant ecogeographic variation in bone size and shape. However, it is unclear how significantly environmental temperature influences cortical and trabecular bone, making it difficult to recognize adaptation versus acclimatization in past populations. There is some evidence that cold‐induced bone loss results from sympathetic nervous system activation and can be reduced by nonshivering thermogenesis (NST) via uncoupling protein (UCP1) in brown adipose tissue (BAT). Here we test two hypotheses: (1) low temperature induces impaired cortical and trabecular bone acquisition and (2) UCP1, a marker of NST in BAT, increases in proportion to degree of low‐temperature exposure. Methods: We housed wildtype C57BL/6J male mice in pairs at 26 °C (thermoneutrality), 22 °C (standard), and 20 °C (cool) from 3 weeks to 6 or 12 weeks of age with access to food and water ad libitum ( N = 8/group). Results: Cool housed mice ate more but had lower body fat at 20 °C versus 26 °C. Mice at 20 °C had markedly lower distal femur trabecular bone volume fraction, thickness, and connectivity density and lower midshaft femur cortical bone area fraction versus mice at 26 °C ( p < .05 for all). UCP1 expression in BAT was inversely related to temperature. Discussion: These results support the hypothesis that low temperature was detrimental to bone mass acquisition. Nonshivering thermogenesis in brown adipose tissue increased in proportion to low‐temperature exposure but was insufficient to prevent bone loss. These data show that chronic exposure to low temperature impairs bone architecture, suggesting climate may contribute to phenotypic variation in humans and other hominins.